Increasing the Motivation for Women of Fertile Age Reproductive Health in Early Cervical Cancer Detection IVA Method with Audiovisual Media - Saputra, Muhammad; Lestari, Agustina (Jurnal Keperawatan Profesional (KEPO), 2025)
Cervical cancer is the leading cause of death that most often occurs in women. This is due to lack of information and late treatment, so in this case providing health education regarding the importance of early detection of cervical cancer with the visual inspection with acetic acid (VIA) which is considered the fastest and cheapest method is very important to do. Using audiovisual media that is interesting and easy to understand so that women can be motivated to do early detection of cervical cancer as soon as possible to reduce mortality and morbidity due to cervical cancer. This type of quantitative research with a quasi-experimental design of a single group pre-test-treatment-post-test, to 38 subjects of fertile women who were taken by accidental sampling, using the Wilcoxon signed rank test. The results of the study showed an increase in motivation to do early detection of cervical cancer with the visual inspection with acetic acid (VIA) after receiving health education through audiovisual media (p-value < 0,05). It was concluded that audiovisual media were very effective for health education in increasing motivation for women to do early detection of cervical cancer with the acetic acid inspection method.